Empowerment of Occupational Therapists in Aquatic Program for Improving the Development of Children with Neurodevelopment Disorder - Saloko, Erayanti; Murti, Bhisma; Adriani, Rita Benya (Journal of Maternal and Child Health, 2017)
Background: Aquatic program is an occupational therapy for children with neurodevelopment disorder that has been recognized as one of the technological innovations in medical rehabilitation. This study aimed to analyze the effectiveness of occupational therapist empowerment training in aquatic program on the knowledge, attitude, and competence of occupational therapists, and the effectiveness aquatic therapy on improving the development of children with neurodevelopment disorder. Subjects and Method: This was a quasi experiment study with pre and post test design with no comparison design. A sample of 88 occupational therapist were selected for this experiment. Knowledge, attitude, and competence of the therapists before and after empowerment training were measured and compared. Likewise, 78 children with neurodevelopmental disorder in Central Java who were under treatment by the occupational therapists were measured and compared before and after the occupational therapist empowerment training, in terms of motoric and sensoric development. The effects of empowerment training on knowledge, attitude, and competence of the occupational therapists as well as motoric and sensoric development of children with neurodevelopment disorder were analyzed by linear regression analysis model. Results: Empowerment training significantly increased knowledge (b=3.95; 95% CI=